2020
DOI: 10.1111/jog.14226
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for typing of cesarean scar pregnancy based on size of cesarean scar diverticulum and its significance in clinical decision‐making

Abstract: Aim: There is currently no universally accepted method for typing of cesarean scar pregnancy (CSP) to guide the choice of treatment approach. We introduce a new method for typing CSP and investigate its clinical significance. Method: Clinical data of 198 patients with CSP were collected and analyzed. The patients were divided into three types according to the size of their cesarean scar diverticula (CSD), measured by magnetic resonance imaging: type I (size of CSD ≤40 mm), type II (40 mm < size of CSD ≤70 mm) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…However, a standardized guideline on uterine-scar evaluation in (early) pregnancy, including CSP, was lacking and different definitions of CSP are in use. Du et al 60 classified CSPs according to the size of the CS diverticula. Kaelin Agten et al 6 classified a CSP as 'on the scar' (partially or fully on top of a well-healed scar) or 'in the niche' (within a deficient or dehiscent scar) depending on the level of invasion of the placenta into the CS scar.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…However, a standardized guideline on uterine-scar evaluation in (early) pregnancy, including CSP, was lacking and different definitions of CSP are in use. Du et al 60 classified CSPs according to the size of the CS diverticula. Kaelin Agten et al 6 classified a CSP as 'on the scar' (partially or fully on top of a well-healed scar) or 'in the niche' (within a deficient or dehiscent scar) depending on the level of invasion of the placenta into the CS scar.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…The TVA and TAS are two common modalities of ultrasound diagnosis to provide effective and important information for the treatment and prognosis of patients. With the development of ultrasound diagnosis technology, the TVA and TAS can detect early ectopic pregnancy and now have become the effective means to assist clinical diagnosis [ 5 , 17 , 18 ]. However, ultrasound diagnosis is susceptible to factors such as intestinal gas in patients and physicians' skill levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the incidence of CSP has increased year by year due to the increased rate of C-sections. Because the CSP has no specific manifestation, it is prone to clinical erroneous diagnosis and missed diagnosis, and failure to timely diagnose and take appropriate care measures will lead to major bleeding, uterine perforation, rupture, and other serious complications in patients [3][4][5]. At present, inquiring the medical history, imaging, and pathological examination are the common methods in clinic to confirm the diagnosis, and surgical exploration is a commonly used examination method in CSP, which is clinically regarded as the examination "gold standard", but it is risky and difficult to promote the application in primary hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Small niches may indeed be quite common but would be clinically unimportant, however, the large niches are most likely to give rise to those complications and should be taken seriously 9,10 . So far, only three small sample studies have defined large niche as a depth of at least 50-80% of anterior myometrium or the remaining myometrial thickness (RMT) less than 2.2 mm when evaluated by TVS [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Large niche incidence has been reported varying from 11% to 45% depending on the definition mentioned above 6 . A recent study indicated that the size of the niche can guide clinical decision and the sum of depth and length greater than 40 mm can increase the failure risk of surgical outcomes 9 . However, research data on large niche development based on large sample sizes is lack.…”
Section: Introductionmentioning
confidence: 99%